Il pollo e il falsario (Lebenswelt. Aesthetics and philosophy of experience., 2019)
In his last teaching Michel Foucault examines the position of the cynical philosopher. This attitude, characterized by a gesture authentically subversive and expressive of a form of life, is assumed and transfigured by the artistic practice of Mauro Folci, who in the performance Smercio di moneta falsa (2016) as Diogene is committed to parakharattein to nomisma (in the two possible readings, equally considered: 'falsify the coin' and 'subvert the costumes').